(untitled) (Clinics, 2022)
Arterial stiffness has been investigated as part of the physiopathology of arterial hypertension since the 1970s. Its role in increasing the “pulsatile load” imposed over the Left Ventricle (LV) has been intensely studied recently and has helped in understanding the mechanisms of Atrial Fibrillation (AF) in hypertensive patients. This paper aims to review the main evidence on this issue and establish possible mechanisms involved in the development of AF in patients with arterial stiffness. A PubMed search was performed, and selected articles were searched for references focusing on this topic. In the long term, lower blood pressure levels allow for arterial wall remodeling, leading to a lower stiffness index. To this day, however, there are no available treatments that directly promote the lowering of arterial wall stiffness. Most classes of anti-hypertensive drugs ‒ with stronger evidence for beta-blockers and diuretics ‒ could be effective in reducing arterial stiffness. There is strong evidence demonstrating an association between arterial stiffness and AF. New studies focusing on arterial stiffness and pre-fibrillatory stages would strengthen this causality relation.